Shaping health communications with behavioral insights: experience from The Bloc - Chu, Magdalene Y. S.; Searle, Ben; Stursi, Michele; Pozzi, Francesco; Rice, Tara (Frontiers in Communication, 2026)
The importance of advancing healthcare through effective communication that speaks directly to healthcare professionals (HCPs) is well recognized. With the landscape of communications changing rapidly, there is an ever greater need to closely assess human behaviors and tailor messages accordingly, such that communications effectively address the concerns of the audience and evoke the appropriate behavioral change. To address this need, The Bloc developed a comprehensive health communications strategy, Behaviorally Enriched Communications (BE-COMMS®). BE-COMMS is based on well-established, validated behavioral models and is developed to ensure communications can be targeted toward specific behavioral barriers and drivers, thereby evoking the desired behavioral change. Consistent application of BE-COMMS in different healthcare communications scenarios has demonstrated that, regardless of geographic location and therapy area, HCPs’ behaviors are influenced by many overt and covert factors related to capability, opportunity, and motivation (as defined in existing behavioral models). While capability and opportunity factors are easily identified, motivational factors are frequently overlooked when designing communications. We also found similarities in HCPs’ behavioral drivers and barriers across different therapeutic areas, but the combination of them in a specific scenario is often unique. Although our analysis is not systematic, it provides a well-rounded overview of factors influencing HCP behavior, as well as our perspective on effectively tailoring communications to bring improvements to patient care. Our accumulated years of practical experience with BE-COMMS demonstrate that communications require a tailored approach for different circumstances to drive behavioral change and improve patient healthcare.